Los múltiples rostros de la objetividad - Macarthur, David (Analysis. Journal of Philosophical Research, 2018)
In this paper I present a positive progressive picture of Putnam's philosophy. Accordingto this way of seeing things, Putnam is a normative cartographer of our linguisticpractices who has over time refined his understanding of the concepts of truth andverification and their complex relationship from discourse to discourse. Looked at inthis way Putnam is primarily a philosopher of objective normativity, who exploresthe various conceptions of objectivity with which we operate as well as resistingthe excesses of both metaphysics and skepticism which do violence to our ordinaryand scientific practices. However, Putnam sees himself as a philosopher of ‘reality’focused on “the realism issue”, a metaphysically inflationary way of thinking that, Iargue, stands in the way of his deepest insights